Moringa (Moringa oleifera L.) Seed Powder as a Bioadsorbent for Heavy Metals in Community Gold Mine Effluent: Implications for Agricultural Water Use - Wantasen, Sofia; Tumbelaka, Selvie; Lumingkewas, Adeleyda M. W.; Paat, Frangky J. (Jurnal Agroekoteknologi Terapan (Applied Agroecotechnology Journal), 2025)
Gold mining in rural areas can contaminate rivers and canals that are also used for irrigation, creating risks for agricultural water use. This study evaluated Moringa oleifera seed powder as a low-cost bioadsorbent to improve community gold mine wastewater in Bolaang Mongondow Timur, North Sulawesi, Indonesia. Effluent collected at the mine outlet was treated in batch with moringa seed powder at 0, 0.5, 1.0 and 1.5 g L⁻¹. Concentrations of Cd, Cr, Cu, Pb and Hg were measured by atomic absorption spectrophotometry before and after treatment, and summarized together with removal efficiencies and Indonesian effluent standards. A dose of 0.5 g L⁻¹ gave the best apparent reduction for Cd and Cu, while Pb and Hg responded best at higher doses; Cr was only weakly affected, consistent with the limited removal of anionic Cr(VI) by unmodified biosorbents. Overall, moringa seed powder reduced the levels of several cationic metals. It may help lower heavy-metal loads entering agricultural water systems. Still, the non-replicated, descriptive nature of the data means that further replicated and field-based studies are needed before routine irrigation use can be recommended. Keywords: Moringa oleifera; bioadsorbent; gold mine wastewater; heavy metals; irrigation water quality